Contact ratio and adaptations in the maxillary and mandibular dentoalveolar joints in rats and human clinical analogs. (December 2022) - Wang, Bo; Nguyen, Nam; Kang, Misun; Srirangapatanam, Sudarshan; Connelly, Stephen; Souza, Richard; Ho, Sunita P.
Abstract: Spatial maps of function-based contact areas and resulting mechanical strains in bones of intact fibrous joints in preclinical small-scale animal models are limited. Functional imaging in situ on intact dentoalveolar fibrous joints (DAJs) in hemimandibles and hemimaxillae harvested from 10 male Sprague-Dawley rats (N = 5 at 12 weeks, N = 5 at 20 weeks) was performed in this study. Physical features including bone volume fraction (BVF), bone pore diameter and pore density, and cementum fraction (CF) of the molars in the maxillary and mandibular joints were evaluated. Biomechanical testing in situ provided estimates of joint stiffness, changes in periodontal ligament spaces (PDL-space) between the molar and bony socket, and thereby localization of contact area in the respective joints. Contact area localization revealed mechanically stressed interradicular and apical regions in the joints. These anatomy-specific contact stresses in maxillary and mandibular joints were correlated with the physical features and resulting strains in interradicular and bony socket compartments. The mandibular joint spaces, in general, were higher than maxillary, and this trend was consistent with age (younger loaded: Mn - 134 ± 55 μm, Mx - 110 ± 47 μm; older loaded: Mn - 122 ± 49 μm, Mx - 105 ± 48 μm). However, a significant decrease (P < 0.05) in mandibular and maxillary joint spaces with age (younger unloaded: Mn - 147 ± 51 μm; Mx - 125 ± 42 μm; older unloaded: Mn - 134 ± 46 μm; Mx - 116 ± 44 μm) was observed. The bone volume fraction (BVF) of mandibular interradicular bone (IR bone) increased significantly with age (P < 0.05) with the percent porosity of coronal mandibular bone lower than its maxillary counterpart. The contact ratio (contact area to total surface area) of maxillary teeth was significantly greater (P < 0.05) than mandibular teeth; both maxillary interradicular and apical contact ratios (IR bone: 41%, 56%; Apical bone: 4%, 12%) increased with age, and were higher than the mandibular (IR bone: 19%, 44%; Apical bone: 1%, 4%) counterpart. Resulting higher but uniform strains in maxillary bone contrasted with lower but higher variance in mandibular strains at a younger age. Anatomy-specific colocalization of physical properties and functional strains in bone provided insights into form-guided adaptive dominance of the maxilla compared to material property-guided adaptive dominance of the mandible. These age-related trends from the preclinical animal model paralleled with age- and tooth position-specific variabilities in mandibular craniofacial bones of adolescent and adult patients following orthodontic treatment. Highlights: In the maxillary and mandibular dentoalveolar joints (DAJs). The surface conformation of bone and cementum are age-specific. An inverse relationship between the contact ratio and functional space exists with age. Age-specific dominance of form over material properties exists. Chewing regimens maintain functional health in the presence or absence of orthodontic forces.